Red clover RNA virus 1: functional analysis of ORF2 protein, associations with co-infecting viruses, and seed transmission - Ekaterina A. Lazareva; Alexander A. Lezzhov; Denis A. Chergintsev; Eugeny A. Tolstyko; Igor V. Selifonov; Anastasia K. Atabekova; Sergey Y. Morozov; Andrey G. Solovyev (Archives of Virology, 2026)

Ir-based oxygen evolution reaction catalysts: Role of microstructure and activation protocols - Margarita V. Kozlova; Elizaveta A. Moguchikh; Anastasia A. Alekseenko; Angelina S. Pavlets; Ilya V. Pankov; Egor E. Aydakov; Vasily V. Kaichev; Maksim A. Solovyev; Irina V. Pushkareva; Dmitri G. Bessarabov; Artem S. Pushkarev (Chemical Engineering Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Hidden diversity of cestode Nippotaenia in a widely distributed invasive fish Perccottus glenii - Sergey G. Sokolov; Pavel G. Vlasenko; Misako Urabe; Dmitry M. Atopkin; Andrey N. Reshetnikov; Peimin Yang; Gelena V. Izotova; Marina B. Shedko; Mikhail M. Solovyev (Hydrobiologia, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Dependence of element composition of bile of freshwater and marine fishes on some abiotic and biotic factors - Mikhail M. Solovyev; Anastasiya V. Shokurova; Olesya V. Anishchenko; Pavel G. Vlasenko; Elena N. Kashinskaya; Karl B. Andree (Frontiers in Marine Science, 2023)
Introduction The elemental composition and physical properties of fish bile is a very important marker for ecotoxicological and physiological studies as bile is able to accumulate elements from environmental compartments. In the present study we focused on the effects of long term (seasons and years) and spatial distance (different water bodies) as well as other biotic (feeding habits, fish species, gut morphology) and abiotic (water salinity) factors on element composition of bile of 429 individuals belonging to 22 forms/species of fishes. Methods Element composition was determined using an inductively coupled plasma optical emission spectrometry. The fishes were analyzed from one marine (the Kandalaksha Gulf of the White Sea), two freshwater oligotrophic (Teletskoye and Baunt lakes), and one freshwater eutrophic water body (Chany Lake). In parallel, we have estimated the volume and density of bile from the same fishes using an automatic pipette and electronic balance. Results and discussion Based on fish bile density and volume data, we hypothesize that gastric fish species (those fishes that have a stomach) require a low volume of bile, but with higher density if compared to agastric fish species (those lacking a stomach) that mainly possessed large volumes of bile, but with a lower density. We have found that the concentrations of the following Na, K, Ca, Mg, S, P (major elements) and Al, Cu, Fe, Sr, Zn (trace elements) were the highest among the 28 elements studied. There were significant findings to contribute to a better understanding of the physiology of bile. First, we have determined the conditions formed in a water body in a given year (season) are more important for element composition of fish bile rather than other tested factors (feeding habits, gut morphology, etc.). Second, the feeding habits of fishes (carnivorous compared to non-carnivorous) had a significant effect based on differences among several elements. Third, the clear distinction between marine and freshwater fishes was found only for K and Na. Understanding which elements are produced as part of waste elimination and those that are present as a consequence of vital biological functions could improve the ecotoxicological study of bile as a marker of heavy metal contamination.

A common founder effect of the splice site variant c.-23 + 1G > A in GJB2 gene causing autosomal recessive deafness 1A (DFNB1A) in Eurasia - Aisen V. Solovyev; Alena Kushniarevich; Elena Bliznetz; Marita Bady-Khoo; Maria R. Lalayants; Tatiana G. Markova; Gabriel Minárik; L’udevít Kádasi; Ene Metspalu; Vera G. Pshennikova; Fedor M. Teryutin; Elza K. Khusnutdinova; et al. (Human Genetics, 2022)

Seasonal variation of the sound-scattering zooplankton vertical distribution in the oxygen-deficient waters of the NE Black Sea - Alexander G. Ostrovskii; Elena G. Arashkevich; Vladimir A. Solovyev; Dmitry A. Shvoev (Ocean Science, 2021)
At the northeastern Black Sea research site, observations from 2010–2020 allowed us to study the dynamics and evolution of the vertical distribution of mesozooplankton in oxygen-deficient conditions via analysis of sound-scattering layers associated with dominant zooplankton aggregations. The data were obtained with profiler mooring and zooplankton net sampling. The profiler was equipped with an acoustic Doppler current meter, a conductivity–temperature–depth probe, and fast sensors for the concentration of dissolved oxygen [O2]. The acoustic instrument conducted ultrasound (2 MHz) backscatter measurements at three angles while being carried by the profiler through the oxic zone. For the lower part of the oxycline and the hypoxic zone, the normalized data of three acoustic beams (directional acoustic backscatter ratios, R) indicated sound-scattering mesozooplankton aggregations, which were defined by zooplankton taxonomic and quantitative characteristics based on stratified net sampling at the mooring site. The time series of ∼ 14 000 R profiles as a function of [O2] at depths where [O2]

Selective Heterozygous Advantage of Carriers of с.-23+1G>A Mutation in GJB2 Gene Causing Autosomal Recessive Deafness 1A - A. V. Solovyev; N. A. Barashkov; F. M. Teryutin; V. G. Pshennikova; G. P. Romanov; A. M. Rafailov; N. N. Sazonov; L. U. Dzhemileva; M. I. Tomsky; O. L. Posukh; E. K. Khusnutdinova; S. A. Fedorova (Bulletin of Experimental Biology and Medicine, 2019)

The short timescale variability of the oxygen inventory in the NE Black Sea slope water - Alexander G. Ostrovskii; Andrey G. Zatsepin; Vladimir A. Solovyev; Dmitry M. Soloviev (Ocean Science, 2018)
Warm winters have recently become common over the Black Sea, leading to the risk of shoaling oxygen penetration. The insufficient supply of oxygen to the near-bottom layer may result in a decrease in faunal abundance. However, there is a lack of data on the temporal variations in oxygen throughout the water column over short timescales of hours to weeks. In this paper, new observations over the upper part of the NE Black Sea continental slope are presented. Regular, frequent measurements were performed using a moored profiler from January to early March 2016. The profiling allowed for direct observations of the temperature in the cold intermediate layer (CIL), pycnocline structure, current velocity, and oxygen stratification and in particular, the depths of hypoxia onset. The average local oxygen inventory below a depth of 30 m was 24.9 mol m−2. Relatively high/low oxygen inventory cases were related to the thin/thick main pycnocline, which was associated with the onshore/offshore location of the Black Sea Rim Current. The pycnocline hindered the vertical transport of oxygenated water to the CIL. The vertical displacements of the hypoxia onset depth ranged from 97 to 170 m, while the shelf edge depth in this region usually ranged from 90 to 100 m. Intermittently, the hypoxia boundary depth fluctuated on two timescales: ∼17 h due to inertial oscillations and 3–7 days due to current meanders and eddies.

Dependence of pH values in the digestive tract of freshwater fishes on some abiotic and biotic factors - M. M. Solovyev; G. I. Izvekova; E. N. Kashinskaya; E. Gisbert (Hydrobiologia, 2018)

Structure of freshwater zooplankton communities from tundra waterbodies in the Lena River Delta, Russian Arctic, with a discussion on new records of glacial relict copepods - E. Abramova; I. Vishnyakova; J. Boike; A. Abramova; G. Solovyev; F. Martynov (Polar Biology, 2017)

Plant-specific 4/1 polypeptide interacts with an endoplasmic reticulum protein related to human BAP31 - Anna V. Pankratenko; Anastasia K. Atabekova; Ekaterina A. Lazareva; Viktoriia E. Baksheeva; Oxana A. Zhironkina; Evgeni Yu Zernii; Robert A. Owens; Andrey G. Solovyev; Sergey Y. Morozov (Planta, 2017)

Feeding habits and ontogenic changes in digestive enzyme patterns in five freshwater teleosts - M. M. Solovyev; E. N. Kashinskaya; G. I. Izvekova; E. Gisbert; V. V. Glupov (Journal of Fish Biology, 2014)
Feeding habits and the activity of digestive enzymes (total alkaline proteases, α ‐amylase and lipase) from dace Leuciscus leuciscus , roach Rutilus rutilus , Prussian carp Carassius auratus gibelio , perch Perca fluviatilis and pikeperch Sander lucioperca fry were studied in the Malye Chany Lake–Kargat Estuary (western Siberia, Russia). The diet of fry from all studied species was mainly composed of chironomid larvae and zooplanktonic organisms ( i.e. cladocera and copepoda), whereas carnivorous species such as P. fluviatilis and S. lucioperca also preyed on fry from other fishes while detritus and microalgae were also important in the diet of ommivorous species. When comparing diet similarity (Sørensen–Dice index, Q S ) among fry at different stages of development, both omnivorous and carnivorous species showed a high level of similarity (0·67 Q S Q S α ‐amylase:total proteases (A:P) values higher than 1 in omnivorous species and lower (A:P ≤ 1) in carnivorous species.

Genome sequences of poa semilatent and lychnis ringspot hordeiviruses - E. I. Savenkov; A. G. Solovyev; S. Y. Morozov (Archives of Virology, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)